2019
DOI: 10.4314/sajas.v49i3.17
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of supplementing broiler diets with a powder mixture of black cumin, Moringa and chicory seeds

Abstract: The present study aimed at evaluating the effect of a phytogenic mixture in the diet on broiler production. A total of 400 day-old unsexed Cobb broiler chicks were randomly allotted to four treatment groups of 10 replications in a randomised design experiment. The phytogenic feed mixture (BMC) contained equal ratios of black cumin, Moringa oleifera and chicory seeds. The treatment groups were as follows: T1 was fed the basal diet, while T2, T3 and T4 were fed the basal diet supplemented with 0.2%, 0.4% or 0.6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 29 publications
1
26
0
1
Order By: Relevance
“…Oxidative stress is usually resulting from the increased production of free-radicals and/or a decrease in the antioxidant mechanism [42][43][44]. Data in Table 5 showed that MDA was significantly reduced in HYSP than in CHSP and HY (1.58 vs. 2.10 and 1.90 nmol/mL, respectively) and it was highest in CH housed ducks (2.54 nmol/mL).…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress is usually resulting from the increased production of free-radicals and/or a decrease in the antioxidant mechanism [42][43][44]. Data in Table 5 showed that MDA was significantly reduced in HYSP than in CHSP and HY (1.58 vs. 2.10 and 1.90 nmol/mL, respectively) and it was highest in CH housed ducks (2.54 nmol/mL).…”
Section: Resultsmentioning
confidence: 99%
“…It is present in tropical and subtropical areas of Asia and Africa. MO is known for its nutritional and pharmacological importance [20][21][22]. All over the world, MO has been extensively and traditionally used to alleviate several afflictions, such as hepatorenal, cardiovascular, hematological, and gastrointestinal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Natural herbalists use the different parts of MO, such as leaves, roots, flowers, fruit, and seeds, to obtain different extracts of Moringa. Among them, Moringa leaf extract is known for its rich contents of calcium, potassium, iron, phosphorous, and vitamins (vitamins A, D, C, E, ascorbic acid, and β-carotene), in addition to natural antioxidants and phytochemical flavonoids, such as polyphenol oxidase, oxidase, and catalase, which has great medicinal importance [20,[25][26][27]. Recent studies focused on the use of MO leaf meal in fish feeds as a cheap and locally available plant, with increasing protein contents [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It might also be due to the bioactive components, which enhance the utilization and efficiency of feed, resulting in improved growth. Plant-derived supplements can minimize the bacterial resistance resulting from the use of antibiotics as growth enhancing supplements ( Abd El-Hack et al., 2018b , Arif et al., 2019 ). Fotina et al.…”
Section: Resultsmentioning
confidence: 99%